Morte, Cultura, memória - Multiplas interseções: Uma interpretação acerca dos cemitérios oitocentistas situados nas cidades do Porto e Belo Horizonte - Marcelina das Gracas de Almeida (2007)
This work has as estimated to evaluate the inherent characteristics to the spaces funereals that they are configured in the eight hundred cemeteries. We understand that the necropolises of century XIX, belonging to its time, reflect the mentality and the imaginary one in which is inserted. The workmanships and images, in them, crystallized disclose basic elements for the understanding of the society and the relations that if establish between the men. Been born in the confluence of a series of factors that pass for the social reorganize, mental politics and; the urbanization, the absorption and application of the medical speeches and hygienists; the consolidation of the bourgeoisie as leading classroom, the supremacy of the individualism and the adoption of new behaviors in relation to deceased and the death. The entombment spaces, at this time, become places of special meaning for the agreement of the feelings and the imaginary one. We intend to point some aspects that propitiate the reflection on the meanings incorporated for the eight hundred necropolises. To cover this way they are distinguished: the decorative epitaphs, elements that decorate the tombs - photographs, statues, adormments amongst others and the use of these places as landmarks of the memory of the great ones, the myth construction and images that distinguish the powerful ones from the other mortals. The main focus of the research is the Cemetery of Nosso Senhor do Bonfim of Belo Horizonte, however the analysis if it extends to the Cemeteries Agramonte and the Prado do Repouso, situated in the city of the Port in Portugal.